Hubungan Body Image dengan Kepercayaan Diri Remaja Putri - Ifdil, Ifdil; Denich, Amandha Unzilla; Ilyas, Asmidir (Jurnal Kajian Bimbingan dan Konseling, 2017)
This study aims to describe the condition of teenage girl’s self-confidence and body image and to identify the relationship between teenage girl's body image with self confidence. This descriptive and correlation study using 77 teenage girls as sample. Sampling technique used stratified random sampling technique. The research used instrument Zila & Ifdil Kepercayaan Diri Inventori and Zila & Ifdil Body Images Inventory. Data were analyzed using descriptive analysis technique and correlational analysis. The findings reveal that teenager girl's self confidence is generally in the medium category, teenage girl's body image is generally in the neutral category, and there is a significant relationship between teenage girl's body image and their self confidence. Teenage girl’s body images and their self confidence are important to be increased and developed by counselor, for their better life towards Indonesian golden generation.